Analysis of Purchase Decisions and Brand Trust at PT Penerbit Erlangga Mahamaru - Aditya Abdullah Permana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the relationship between purchasing decisions and brand trust at PT Publisher Erlangga Mahamaru, located in the South Jakarta area. The primary objective of this research is to investigate the direct and indirect effects of promotion, product knowledge, and price fairness on purchasing decisions, with brand trust serving as a mediating variable. A quantitative approach was employed, and data were collected from a sample of 229 customers of PT Publisher Erlangga Mahamaru. The data were analyzed using partial least squares structural equation modeling (PLS-SEM), which is appropriate for testing complex relationships among multiple variables. The findings indicate that promotion, product knowledge, and price fairness each have a significant direct impact on purchasing decisions. Additionally, both promotion and product knowledge are found to have a significant positive effect on brand trust, whereas price fairness does not significantly affect brand trust. Furthermore, the study reveals indirect effects through the mediating role of brand trust: promotion and product knowledge influence purchasing decisions through brand trust, confirming its mediating effect for these two variables. In contrast, price fairness does not exhibit a significant indirect effect on purchasing decisions via brand trust. These results highlight the critical roles of promotion and product knowledge in fostering brand trust and ultimately enhancing purchasing decisions. In contrast, while price fairness contributes directly to purchasing decisions, it does not strengthen brand trust. Therefore, managers should prioritize strategies that improve promotional activities and increase customers’ product knowledge to build brand trust, which in turn can drive stronger purchasing decisions.